(untitled) (Scientific journal of the Fergana State University, 2023)
The topic of stimulating students’ knowledge activity is in the center of attention of professors and teachers, where the main focus is on teaching biology in non-traditional ways. In this article, J. Tolipova and A.T.Gofurova’s research of some sources have been analyzed. In addition, the textbooks of scientists A.M. Kadirov, A.G. Akhmedov, who made a great contribution to the science of human anatomy, were also discussed. Knowing the educational processes, principles and laws related to the basics of biology allows the teacher to organize and manage the educational processes related to the school biology course in accordance with the requirements of the time. This is the purpose of introducing the content of biological subjects, its teaching forms, methods, and tools in a mutually dependent manner, to provide in-depth knowledge of biological subjects, and to develop them as a comprehensively developed person. requires effective use of innovative educational technology that helps to find. The biology teaching methodology aims to introduce the content of biology subjects, its teaching forms, methods, and tools in a mutually dependent manner.